Embolic mycotic encephalitis in a cow following Mortierella wolfii infection of a surgery site. (September 2017) - Curtis, Benjamin; Hollinger, Charlotte; Lim, Ailam; Kiupel, Matti
A 5-y-old Holstein dairy cow had surgery for a suspected displaced abomasum 10 d postpartum, developed acute neurologic signs at day 19, and was found dead 21 d postpartum. At autopsy, there was a peri-incisional intramuscular abscess that communicated with the peritoneal cavity, as well as hemorrhage and malacia involving the brain, and multiple nodules in the liver, kidneys, and lungs. Fungal hyphae were seen histologically at the surgery site, on the surface of the liver, and in lesions of severe necrotizing vasculitis in the lungs, kidneys, brain, and liver. The uterus was free of fungal organisms. Pan-fungal PCR and DNA sequencing identified the fungus as Mortierella wolfii . Previously reported deaths from M. wolfii have been related to abortion, but in this case, there was no histologic evidence of fungal organisms in the uterus, calving was routine, and there was a several week delay between calving and development of neurologic signs. The findings suggested a unique case of surgical site infection with subsequent embolic mycosis.